2008
DOI: 10.1177/1084713807313085
|View full text |Cite
|
Sign up to set email alerts
|

Causation of Permanent Unilateral and Mild Bilateral Hearing Loss in Children

Abstract: kHz) in 1 or both ears with air-bone gaps at 3.0 and 4.0 kHz no greater than 10 dB. On average, children with these losses have high academic failure rates as compared with those of their normal hearing peers. 1,3,6 The psychoeducational and psychosocial implications of UHL and MBHL are reviewed earlier in this issue by Tharpe.8 Despite considerable interest in the effects of these losses on child development, little attention has been paid to the underlying etiologies. In fact, contemporary reports of causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 77 publications
(127 reference statements)
0
34
0
4
Order By: Relevance
“…Since complete deafness was an exclusion criterion for EDSP study participation at baseline, the impairment assessed referred to a period of transient or permanent severe HI. The most common causes of severe hearing loss that may temporarily or permanently affect young people include syndromal or non-syndromal genetic disorders, prenatal and perinatal infections and noise exposure (for reviews, see Olusanya & Newton, 2007 ;Tharpe & Sladen, 2008).…”
Section: T0-t3 Assessment Of Himentioning
confidence: 99%
See 1 more Smart Citation
“…Since complete deafness was an exclusion criterion for EDSP study participation at baseline, the impairment assessed referred to a period of transient or permanent severe HI. The most common causes of severe hearing loss that may temporarily or permanently affect young people include syndromal or non-syndromal genetic disorders, prenatal and perinatal infections and noise exposure (for reviews, see Olusanya & Newton, 2007 ;Tharpe & Sladen, 2008).…”
Section: T0-t3 Assessment Of Himentioning
confidence: 99%
“…Numerous conditions in young people may affect hearing acuity, resulting in transient or permanent impairment (for reviews, see Olusanya & Newton, 2007 ;Tharpe & Sladen, 2008). Causes of HI in young people that may also have an impact on the risk for psychotic experiences include birth trauma (Herrgard et al 1995) and prenatal and postnatal exposure to infections (Dalman et al 2008 ;Zammit et al 2009).…”
Section: Hi and Psychosis : A Shared Cause ?mentioning
confidence: 99%
“…Thus, UHL may be a risk factor for children's language development and academic achievement, since they might present difficulties in daily communication and hearing situations (6) . Studies have shown that 1/3 of children with permanent unilateral hearing loss present language and learning delays (7,8,9) . A study conducted at the Colorado Home Intervention Program (10) noticed that nearly 33% of its subjects presented language development below the expected for their age groups.…”
Section: Introductionmentioning
confidence: 99%
“…En sık görülen nedenler arasında viral enfeksiyonlar (yaklaşık %25), menenjit (%15), iç kulak yokluğundan geniş vestibüler aquaduktus sendromuna kadar değişen iç kulak anomalileri, işitme siniri yokluğu, kafa travması, ototoksik ilaç kullanımı, tümörler, ani işitme kaybı ve işitsel nöropati sayılabilir. [12] Doğuştan işitme kayıpları açısından önemli olan risk faktörleri tek taraflı işitme kayıpları için de araş-tırılmıştır. Buna göre yenidoğan döneminde tek taraflı işitme kaybı tanısı konulan bebeklerin %30'unda risk faktörü bulunmuştur ve en sık bulunan risk kraniyofasiyal anomalilerdir.…”
Section: Eti̇yoloji̇unclassified
“…Bakteriyel menenjit ise farklı çalışmalarda %4-30 oranında bildirilmiştir. [12,16] Ani işitme kaybı çoğunlukla tek taraflı olarak görü-lür. Olguların ancak %2 kadarı iki taraflıdır.…”
Section: Eti̇yoloji̇unclassified